"If We Could Just Sit down and Talk": Fathers' Partnerships with Educational Professionals. Issue 3 (27th May 2022) - Pancsofar, Nadya; Petroff, Jerry G.
ABSTRACT: Family-professional partnerships are an important predictor of student success for children with and without disabilities. However, little is known about the perspectives of fathers of children with complex disabilities regarding their partnerships with educational professionals. This study presents findings from semi-structured interviews with 15 fathers of children with complex disabilities regarding their partnerships with professionals. Fathers described both challenging and collaborative interactions with the educational professionals working with their children. In challenging interactions, fathers described educational professionals focused on the monetary costs of their child's educational needs, a struggle to find schools and programs that fit their child's needs, and educators who were inflexible and unwilling to implement individualized instructional strategies. More positive and collaborative father-professional partnerships were characterized by authentic relationships that responded to the expertise of parents, as well as educators who were flexible and strengths-based in their practice. Fathers offered guidance for how educators could strengthen partnerships with fathers. Findings from this study extend the very limited research on the school involvement experiences of fathers of children with complex disabilities by identifying specific characteristics of positive and negative family-professional interactions for these fathers and highlighting avenues for change in professional practice to strengthen fathers' school involvement experiences.